Mygalin: An Acylpolyamine With Bactericidal Activity - Espinoza-Culupu, Abraham (2020)
Inappropriate use of antibiotics favors the selection and spread of resistant bacteria. To reduce the spread of these bacteria, finding new molecules with activity is urgent and necessary. Several polyamine analogs have been constructed and used to control microorganisms and tumor cells. Mygalin is a synthetic acylpolyamine, which are analogs of spermidine, derived from the hemolymph of the spider Acanthoscurria gomesiana. The effective activity of polyamines and their analogs has been associated with their structure. The presence of two acyl groups in the Mygalin structure may give this molecule a specific antibacterial activity. The aim of this study was to identify the mechanisms involved in the interaction of Mygalin with Escherichia coli to clarify its antimicrobial action. The results indicated that Mygalin exhibits intense dose and time-dependent bactericidal activity. Treatment of E. coli with this molecule caused membrane rupture, inhibition of DNA synthesis, DNA damage, and morphological changes. The esterase activity increased along with the intracellular production of reactive oxygen species (ROS) after treatment of the bacteria with Mygalin. In addition, this molecule was able to sequester iron and bind to LPS. We have shown that Mygalin has bactericidal activity with underlying mechanisms involving ROS generation and chelation of iron ions that are necessary for bacterial metabolism, which may contribute to its microbicidal activity. Taken together, our data suggest that Mygalin can be explored as a new alternative drug with antimicrobial potential against Gram-negative bacteria or other infectious agents.